Bushfire safety - Healey, Justin (Issues in society (Balmain, N.S.W.) ;, 2018)
Explores the basics of bushfires, how and where they occur, the threats they pose and their hazards. The book also explains in detail how to effectively prepare your home for a bushfire, and when to safely leave. Future bush fires are expected to get worse. Learn now how to prepare, act and survive. Also includes: worksheets and activities, fast facts, glossary, web links, index.